March 8 eclipsing May 13 - Ooi, Kee Beng 1955- (Institute of Southeast Asian Studies, 2008)
For a whole generation of Malaysians, no proper closure to the traumas of the racial riots of May 13, 1969 has been possible. But then came March 8, 2008 The surprising results of the General Election on that special day have started eclipsing the fears linked for so long to that spectral night forty years ago. All the three researchers from ISEAS who each authored separate chapters for this book were in different parts of Malaysia monitoring its 12th General Election during the thirteen days of campaigning. Their analyses provide new insights into the phenomenon that Malaysians now simply refer to as "March 8". Ooi Kee Beng scrutinizes in detail the electoral campaign in the state of Penang, Johan Saravanamuttu studies the case of Kelantan state and the elections in general, while Lee Hock Guan examines changes in the voting pattern in the Klang Valley